Bismuth oxide as a high capacity anode material for sodium-ion batteries. Issue 79 (12th September 2016) - Kim, Min-Kun; Yu, Seung-Ho; Jin, Aihua; Kim, Jin; Ko, In-Hwan; Lee, Kug-Seung; Mun, Junyoung; Sung, Yung-Eun
Abstract : A bismuth oxide electrode, delivering high capacity, as an anode material for sodium-ion batteries was simply prepared. Abstract : A bismuth oxide electrode, delivering high capacity, as an anode material for sodium-ion batteries was simply prepared. The electrochemical properties of bismuth oxide were studied by operando X-ray absorption near edge structure spectroscopy and ex situ X-ray diffraction methods. A bismuth oxide/carbon composite showed enhanced cycle stability at high current densities.